STUDY OF XANTHOMONAS CAMPESTRIS PV. CAMPESTRIS ISOLATES ORIGINATING FROM SOIL AND BRASSICA SPP. SEEDS - Vlajić, Slobodan; Gvozdanović Varga, Jelica; Iličić, Renata (Emirates Journal of Food and Agriculture, 2022)
Xanthomonas campestris pv. campestris (Xcc) is a harmful pathogen of the Brassicaceae agricultural plants in Serbian agroecological conditions. The bacterium survives in soil, plant residues, seeds, and wild and weedy plants. This study aimed to characterize Xcc isolates that persist in field soil and roots where they represent a risk to causing disease of Brassicaceae plants. Collection of soil samples was carried out in the period 2015 - 2017 in four locations regions Vojvodina with cabbage cultivation in monoculture or crop rotations. The cabbage seed samples were collected in the same period in Futog and Despotovo locations (agricultural farms) and local farmer markets. All isolations were done on SX and YDC agar plates with the addition of cycloheximide at 250 mg/l. Based on the pathogenicity tests and morphological and biochemical characteristics, 28 identified Xcc isolates were selected, 12 from soil and 16 from seeds. Molecular confirmation of the Xcc isolates was done using multiplex PCR (m-PCR) with Xcc-specific primer sets DLH 120/125 and Zup 2309/2310. In all selected isolates and the reference Xcc strain NCPPB1144, the expected 370 and 619 bp PCR fragments were amplified. Characterizing isolates by rep-PCR fingerprinting using BOX A1R and (GTG)5 primers resulted in informative patterns. Cluster analysis grouped the strain Xcc NCPPB 1144 with all Xcc isolates, while other tested Xanthomonads were clustered separately. Based on the similarity level of 90%, we obtained three out of 12 representative isolates from soil and four out of 16 representative seed isolates. The characterization of Xcc isolates from soil and seeds will enable their comparison with those pathogenic isolated from leaves of Brassicaceae plants.